2D in situ determination of soot optical band gaps in flames using hyperspectral absorption tomography - Bauer, Florian; Bräuer, Phillipp; Wilke, Marius; Will, Stefan; Grauer, Samuel J. (Combustion and Flame, 2023)
During the formation of soot, the particles undergo a fine structural transformation, akin to graphitization, from “young” to “mature” soot. This ageing process is accompanied by a change in optical properties, which manifests in the soot optical band gap and dispersion exponent, Eg and ζ. Although both quantities are regularly determined via broadband extinction measurements, they have a nonlinear relationship to the local extinction spectrum, so line-of-sight integrated measurements introduce errors into estimates of Eg and ζ. We report the development of an absorption tomography sensor that enables 2D in situ mapping of Eg and ζ. Our sensor employs broadband back-illumination, fiber-coupled collection optics, and an imaging spectrograph to simultaneously acquire 24 spectrally-resolved absorption signals, suitable for tomographic reconstruction. We perform proof-of-concept experiments to characterize soot formation in non-premixed steady flames from a Gülder burner, using ethylene and propane as fuels. Reconstructions based on axisymmetric and non-axisymmetric absorption tomography are compared, and we explore how our sensor can be adapted to perform temporally-resolved measurements in a turbulent flame.
CRIS-Team Scopus Importer:2023-04-14
Keywords: Absorption tomography; Dispersion exponent; In situ diagnostics; Non-premixed co-flow flame; Soot optical band gap

3D mapping of polycyclic aromatic hydrocarbons, hydroxyl radicals, and soot volume fraction in sooting flames using FRAME technique - Chorey, Devashish; Kögl, Matthias; Boggavarapu, Prasad; Bauer, Florian; Zigan, Lars; Will, Stefan; Ravikrishna, R. V.; Deshmukh, Devendra; Mishra, Yogeshwar Nath (Applied Physics B-Lasers and Optics, 2021)
We report the three-dimensional (3D) mapping of polycyclic aromatic hydrocarbons (PAHs), soot, and hydroxyl radicals (OH) in ethylene/air diffusion flames. A structured illumination-based frequency recognition algorithm for multiple exposures (FRAME) approach is combined with sample translation to intersect the flame in several two-dimensional planes. The FRAME technique has been used for recording a snapshot of multiple species on a single camera. It relies on extracting the amplitude of spatial modulation of two or more probed species encoded on a single sub-image. Here, the FRAME technique is first applied for simultaneous imaging of PAH by laser-induced fluorescence (PAH-LIF) and soot by laser-induced incandescence (LII). Sequentially, it is employed for simultaneous mapping of OH-LIF and soot-LII. The LII signal is converted to absolute soot volume fraction (fv) maps using a line-of-sight light extinction measurement. Finally, we have demonstrated the approach for layer-wise 2D imaging of soot volume fraction and averaged 3D mapping of multiple species.
CRIS-Team Scopus Importer:2021-10-22

4D temperature measurements using tomographic two-color pyrometry - Yu, Tao; Bauer, Florian; Huber, Franz; Will, Stefan; Cai, Weiwei (Optics Express, 2021)
This work presents a new approach for high-speed four-dimensional (3D+t) thermometry using only two high-speed cameras which are equipped with different band pass filters to capture thermal radiation signals at two narrow wavelength bands. With the help of a customized fiber bundle and a beam splitter, a total number of nine projections at each band were recorded, and the temperature distribution was evaluated by tomographic two-color pyrometry. In order to validate the effectiveness of this method, the 3D temperature distribution of a premixed steady flat flame was evaluated. The determined temperatures were compared to those of other studies, as well as to the results from inverse Abel transform and line-of-sight data. Further, the 3D temperature evolution of a weakly turbulent diffusion flame was observed at a repetition rate of 7.5 kHz. Such 4D temperature measurements are expected to be valuable in understanding turbulent combustion mechanisms especially of practical device

Analysis of the LIF/Mie Ratio from Individual Droplets for Planar Droplet Sizing: Application to Gasoline Fuels and Their Mixtures with Ethanol - Kögl, Matthias; Baderscheider, Kevin; Bauer, Florian; Hofbeck, Bernhard; Berrocal, Edouard; Will, Stefan; Zigan, Lars (Applied Sciences, 2019)
Keywords: laser-induced fluorescence; nile red; Mie scattering; gasoline; model fuel; ethanol

Burner-heated dehydrogenation of a liquid organic hydrogen carrier (LOHC) system - Bollmann, Jonas; Mitländer, Kerstin; Beck, Dominik; Schühle, Patrick; Bauer, Florian; Zigan, Lars; Wasserscheid, Peter; Will, Stefan (International Journal of Hydrogen Energy, 2023)
For a hydrogen-based economy, safe and efficient hydrogen storage is essential. Compared to other chemical hydrogen storage technologies, such as ammonia or methanol, liquid organic hydrogen carrier (LOHC) systems allow for a reversible storage of hydrogen while being easy to handle in a diesel-like manner. In our contribution, we describe for the first time the successful utilization of the exhaust gas enthalpy of a porous media burner to directly supply the dehydrogenation heat for a kW-scale dehydrogenation of the hydrogen-rich LOHC compound perhydro dibenzyltoluene (H18-DBT). Our setup demonstrates the dynamics of the dehydrogenation unit at a realized maximum hydrogen power of 3.9 kWth, based on the lower heating value of the released hydrogen. For the intended applications with fluctuating hydrogen demand, e.g. a hydrogen refueling station (HRS) or stationary heating in buildings, a dynamic hydrogen supply from LOHC is important. Methane, e.g. from a biogas plant, is utilized in our scenario as a fuel source for the burner. Hydrogen is released within 30 min after cold start of the system. The dehydrogenation unit exhibits a power density relative to the reactor volume of about 0.5 kWtherm l−1 based on the lower heating value of the hydrogen and a catalyst productivity of up to 0.65 gH2 gPt−1 min−1 for hydrogen release from H18-DBT. An analysis of the by-products and reaction intermediates shows low by-product formation (e.g. maximum 0.6 wt.-% for high boilers and 0.9 wt.- % for low boilers) and uniform distribution of intermediates after the reaction. Thus, a relatively homogeneous temperature distribution and a uniform LOHC flow in the reaction zone can be assumed. Our findings illustrate the dynamics (heating rates of about 10 K min−1) and performance of direct heating of a release unit with a burner and represent a significant step towards LOHC-based hydrogen provisioning systems at technically relevant scales.
CRIS-Team Scopus Importer:2023-09-01
Keywords: Dehydrogenation; Dynamic heat supply; Hydrogen storage; LOHC; Porous media burner

Can soot primary particle size distributions be determined using laserinduced incandescence? - Bauer, Florian; Daun, Kyle James; Huber, Franz; Will, Stefan (8th International Workshop on Laser-Induced Incandescence, 2018)

Can soot primary particle size distributions be determined using laser‑induced incandescence? - Bauer, Florian; Daun, Kyle James; Huber, Franz; Will, Stefan (Applied Physics B-Lasers and Optics, 2019)
Soot from combustion processes often takes the form of fractal-like aggregates, assembled of primary particles, both of which obey polydisperse size distributions. In this work, the possibility of determining the primary particle size distribution through time-resolved laser-induced incandescence (TiRe-LII) under the influence of thermal shielding of polydispersely distributed aggregates is critically investigated for two typical measurement situations: in-flame measurements at high temperature and a soot-laden aerosol at room temperature. The uncertainty attached to the quantities is evaluated through Bayesian inference. We show how different kinds of prior knowledge concerning the aggregation state of the aerosol affect the uncertainties of the recovered size distribution parameters of the primary particles. To obtain reliable estimates for the primary particle size distribution parameters, specific information about the aggregate size distribution is required. This is especially the case for cold bath gases, where thermal shielding has a large effect. Furthermore, it is crucial to use the full duration of the usable LII signal trace to recover the width of the size distribution with small uncertainties. The uncertainty attached to TiRe-LII inferred primary particle size parameters becomes considerably larger when additional model parameters are considered.<br

Characterisation of the transition type in optical band gap analysis of in-flame soot - Bauer, Florian; Bräuer, Phillipp; Aßmann, Simon; Thiele, Maximilian A.; Huber, Franz; Will, Stefan (Combustion and Flame, 2022)
Semiconductor materials are characterised by a band gap between conduction and valence band, which can either be of direct or indirect nature depending on the crystal momentum. In case of applying the so-called Tauc method to infer the band gap value, both transition types are described by different values for the transition type exponent. In the case of soot particles, the optical band gap is an important quantity during the evolution process to describe the optical characteristics mainly linked to the underlying structural properties. In this work, an approach to infer the optical band gap value together with the transition type exponent is used to shed light on the electronic nature and optical properties of soot during its formation process. In situ UV–Vis-NIR extinction measurements as well as ex situ Raman spectroscopy are performed in a non-premixed ethylene/air flame at two different positions in the flame reflecting different stages of the soot formation process. The results reveal two important tendencies: first, an increase in the band gap energy of young soot is observed, possibly caused by the curvature of initially planar polycyclic aromatic hydrocarbon monomers due to the presence of odd-numbered rings in the hexagonal aromatic lattice. Second, a decrease of the transition type exponent value can be observed, indicating a shift from an indirect transition to a more direct band structure. Further, the indirect band gap assumption for mature soot and its band gap value close to 0.2 eV can be confirmed experimentally. The Raman results provide additional insight in the atomic fine structure of the soot particles regarding the defect density and the loss of amorphous character with increasing maturity.
CRIS-Team Scopus Importer:2022-01-28
Keywords: Raman spectroscopy; Soot band gap energy; Soot formation; Tauc method; Transition type

Comprehensive morphological characterization of industrial nano-aerosols by optical measurement methods - Aßmann, Simon; Bauer, Florian; Huber, Franz; Will, Stefan (International Conference on Advanced Optical Technologies, 2019)

Correction procedure for a tomographic optical setup employing imaging fiber bundles and intensified cameras - Müller, Marcel; Bauer, Florian; Cai, Weiwei; Huber, Franz; Will, Stefan (Applied Optics, 2024)
For reliable tomographic measurements the underlying 2D images from different viewing angles must be matched in terms of signal detection characteristics. Non-linearity effects introduced by intensified cameras and spatial intensity variations induced from inhomogeneous transmission of the optical setup can lead, if not corrected, to a biased tomographic reconstruction result. This paper presents a complete correction procedure consisting of a combination of a non-linearity and flatfield correction for a tomographic optical setup employing imaging fiber bundles and four intensified cameras. Influencing parameters on the camera non-linearity are investigated and discussed. The correction procedure is applied to 3D temperature measurements by two-color pyrometry and compared to results without correction. The present paper may serve as a guideline for an appropriate correction procedure for any type of measurement involving optical tomography and intensified cameras.
CRIS-Team Scopus Importer:2024-01-12

Determination of the absorption function of laser-heated soot particles from spectrally resolved laser-induced incandescence signals using multiple excitation wavelengths - Lang, Peter; Bräuer, Phillipp; Müller, Marcel; Faderl, Sebastian R.; Huber, Franz; Bauer, Florian; Will, Stefan (Applied Physics B-Lasers and Optics, 2023)
In this work, the optical properties of soot particles from a Gülder burner fueled with both ethylene or propane gas were investigated in situ using laser-induced incandescence. The particles in the flame were irradiated with four different laser wavelengths, namely 450 nm, 532 nm, 600 nm and 650 nm. The resulting laser-induced emissions were detected spectrally and temporally resolved by means of a spectrograph and an intensified camera at different delay times with respect to the laser pulse. To determine the optical properties of the particles from the data, the emitted spectra were simulated using a spectroscopic model with variable input parameters, and a regression was performed against the measured data. On the basis of an functional approach of the absorption function on wavelength, the dispersion exponent for soot was evaluated for a reference position on the centre axis at 40 mm height above the burner. It was found that the different fuel gases lead to similar values with regard to the absorption function, which can be expressed by a mean dispersion exponent with a value of 1.75 for ethylene and 1.68 for propane.
CRIS-Team Scopus Importer:2023-09-08

Determination of various absorbing species in sooting flames using UV-VIS-absorption-spectroscopy - Bauer, Florian; Huber, Franz; Will, Stefan (International Conference on Advanced Optical Technologies, 2019)

Dreidimensionale Bestimmung von Rußpartikelgröße und Rußkonzentration mittels tomographischer Laserinduzierter Inkandeszenz - Bauer, Florian; Yu, Tao; Cai, Weiwei; Huber, Franz; Will, Stefan (Jahrestreffen 2021 der ProcessNet-Fachgruppen „Gasreinigung“ und „Partikelmesstechnik“, 2021)

Impact of polarization and detection angle on Mie scattering signals for planar droplet sizing - Klevansky, Benjamin; Mishra, Yogeshwar Nath; Lehnert, B. L.; Wensing, M.; Bauer, Florian; Will, Stefan (Experiments in Fluids, 2025)
Abstract: The planar droplet sizing (PDS) method for determining the droplet diameter from the ratio of laser-induced fluorescence (LIF) and Mie scattering signal (Mie) has been extensively applied for right-angle scattering detection. The present work consists of a parametrical study of the Mie signal dependency on the scattering angle and polarization, as well as further experimental investigations in single droplets to ultimately improve the intensity fluctuation characteristics of the signal through a favorable experimental arrangement. Finally, we investigated how these findings impact droplet sizing in a spray on a shot-to-shot basis, as well as averaged across a dataset, via microscopic and macroscopic spray measurements. In the parametrical study, we found that horizontally polarized incident light results in a higher degree of Mie signal fluctuation than vertically polarized incident light at a scattering angle of Θ=90∘, whereas the reduction to Θ=60∘ resulted in the exact opposite observation. Furthermore, the reduction from Θ=90∘ to Θ=60∘ resulted in an overall improvement to the D2-dependency and signal fluctuation of the Mie signal. We observed the effects shown in the parametric study in the experimental droplet measurements. For instance, when observing single droplets, the change from Θ=90∘ to Θ=60∘ resulted in a reduction in signal fluctuation by 46.1% and 17.6% for horizontally and vertically polarized incident light, respectively. An implementation into a spray setup yielded reduced shot-to-shot sizing deviations and closer adherence to the microscopically measured diameter when averaged across the dataset.
CRIS-Team Scopus Importer:2025-01-31

Inferring soot morphology through multi-angle light scattering using an artificial neural network - Talebi Moghaddam, Sina; Bauer, Florian; Huber, Franz; Will, Stefan; Daun, Kyle James (Journal of Quantitative Spectroscopy & Radiative Transfer, 2020)
The morphological parameters of polydisperse aerosolized soot can be found by regressing modeled angularly-resolved elastic light scattering to experimental measurements, but this is an ill-posed problem in the presence of measurement noise or model error. Rayleigh-Debye-Gans Fractal Aggregate (RDG-FA) theory provides a closed-form solution for the light scattering kernel in the measurement model but can be subject to 30% model error (or more) compared to the exact solution, which is amplified by the ill- posedness of the inference problem into significant errors in the recovered morphological parameters. More precise approaches, e.g. the multi-sphere T-matrix method (MSTM), are too expensive for inference problems, which require repeated evaluation of the forward model; this is particularly true when com- puting posterior probability densities and credibility intervals. In this work, a computationally-efficient artificial feed-forward multi-layered neural network (ANN) is trained using MSTM scattering simulations on randomly-generated soot aggregates sampled from plausible morphological parameters. A fixed value is specified for the refractive index, while the monodisperse primary particle diameters are specified, and sintering, overlap or necking phenomena are ignored for the MSTM simulations. The ANN is then used to approximate the light scattering kernel in the measurement model, which is incorporated into the Bayesian inference procedure. The Bayesian/ANN approach is shown to be more accurate compared to a Bayesian approximation error technique. The Bayesian/ANN is then applied to in-flame measurements of soot and results are compared with transmission electron microscopy results from the literature. Pa- rameters derived from electron micrographs of extracted soot are not contained within 90% credibility intervals; this is likely due to some of the simplifying assumptions in the scattering model, which points the way towards future work.<br
Keywords: Nanoparticle; Soot; Fractal aggregates; Elastic light scattering; Bayesian analysis; Artificial neural network; Machine learning; Principal component analysis; Size distribution; Credibility intervals; Rayleigh-Debye-Gans; MSTM

Inferring the Morphology of Cabonaceous Nanoparticles Through Light Scattering: a Bayesian Artificial Neural Netzwork Approach - Talebi Moghaddam, Sina; Bauer, Florian; Huber, Franz; Will, Stefan; Daun, Kyle James (Nano Ontario Conference 2019, 2019)

In situ characterisation of absorbing species in stationary premixed flat flames using UV–Vis absorption spectroscopy - Bauer, Florian; Degenkolb, Michael U. J.; Huber, Franz; Will, Stefan (Applied Physics B-Lasers and Optics, 2021)
A one-dimensional premixed ethylene–air flame is investigated regarding the presence of various combustion intermediates and products relevant for the formation of carbonaceous particles for various equivalence ratios and spatial positions using in situ UV–Vis absorption spectroscopy. A laser driven light source in combination with a fast spectrometer allow to record absorption spectra at a high rate required for practical combustion devices. The approach is coupled with a least squares regression procedure using a database of several absorbing species in the flame. To account for the high temperature flame conditions, the absorption spectra are convoluted by a simplified Maxwell–Boltzmann distribution model. While the approach is based on several assumptions and a verification requires future detailed intercomparison with other techniques, a first semi-quantitative evaluation can be obtained. This novel approach opens a potential route to the in situ measurement of the evolution of polycyclic aromatic hydrocarbons (PAHs) in flames.

In situ characterization of absorbing species in flames using UV-vis-spectroscopy - Bauer, Florian; Huber, Franz; Will, Stefan (37th International Symposium on Combustion, 2018)

In-situ UV-VIS-absorption-spectroscopy measurements in a stationary premixed flat flame for the characterization of soot and polycyclic aromatic hydrocarbons - Bauer, Florian; Ulrich, Hannah; Huber, Franz; Will, Stefan (Gordon Research Conference on Laser Diagnostics in Energy and Combustion Science, 2019)

Investigation of Soot Formation by Optical Diagnostics: From Precursor Measurements to 3D Particle Sizing - Bauer, Florian (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2023)

Investigation of soot formation in 2D by combined multi-angle light scattering and laser-induced incandesence employing a shielding approach - Aßmann, Simon; Altenhoff, Michael; Perlitz, Julian; Bauer, Florian; Huber, Franz; Will, Stefan (8th International Workshop on Laser Induced Incandescence, 2018)

Messtechnische Grenzen bei der Bestimmung von Primärpartikelgrößenverteilungen mittels Laserinduzierter Inkandeszenz - Bauer, Florian; Daun, Kyle James; Huber, Franz; Will, Stefan (Jahrestreffen der ProcessNet-Fachgruppe Partikelmesstechnik und des Arbeitsausschusses Feinstäube, 2020)

Morphology-dependent resonances in laser-induced fluorescence images of micrometric gasoline/ethanol droplets utilizing the dye nile red - Kögl, Matthias; Dai, Hongfei; Qomi, Mohammad Pahlevani; Bauer, Florian; Eppinger, Bernd; Zigan, Lars (Applied Optics, 2021)
The present study deals with the solvent-dependent morphology-dependent resonances (MDR) in the laser-induced fluorescence (LIF) signal of monodisperse gasoline droplets (30 mu m-60 mu m) generated with a droplet generator. To investigate the influence of an ethanol addition to gasoline and the respective LIF signal of the dye nile red dissolved in these fuel blends, a reference gasoline fuel is blended with various ethanol concentrations from E0 (gasoline) to E100 (pure ethanol). A spectral fluorescence characterization of the investigated fuel mixtures at various concentrations is carried out in a micro cell in order to identify the dye and ethanol concentration influence of the respective fuel mixtures. The absorption and emission spectra of the fuel mixtures show a Stokes shift with increasing ethanol concentration towards larger wavelengths. The coefficient of variation (COV) of the fluorescence signals of spherical droplets was utilized to characterize the MDR effects within the droplet LIF images. The investigations revealed an increase of MDR contribution in terms of the COV of LIF signals with larger droplet diameters. For small droplets, no monotonic trend was found for contribution of MDR in the LIF signal as a function of the ethanol concentration. For larger droplets (e.g., 50 mu m-60 mu m), a lower contribution of MDR in LIF signals was observed with increasing ethanol content. For E80 and most of the studied ethanol blends, the normalized integrated COV values exhibited maxima at certain droplet sizes (40 mu m, 47.5 mu m and 55 mu m), which indicate the presence of distinct MDR effects. (C) 2021 Optical Society of America
CRIS-Team WoS Importer:2021-06-25

Neutral bremsstrahlung emission in laser-induced incandescence experiments on soot and silver nanoparticles - Talebi Moghaddam, Sina; Bauer, Florian; Huber, Franz; Daun, Kyle James; Will, Stefan (8th International Workshop on Laser-Induced Incandescence, 2018)

Single-pulse real-time billion-frames-per-second planar imaging of ultrafast nanoparticle-laser dynamics and temperature in flames - Mishra, Yogeshwar Nath; Wang, Peng; Bauer, Florian; Zhang, Yide; Hanstorp, Dag; Will, Stefan; Wang, Lihong V. (Light: Science & Applications, 2023)
Unburnt hydrocarbon flames produce soot, which is the second biggest contributor to global warming and harmful to human health. The state-of-the-art high-speed imaging techniques, developed to study non-repeatable turbulent flames, are limited to million-frames-per-second imaging rates, falling short in capturing the dynamics of critical species. Unfortunately, these techniques do not provide a complete picture of flame-laser interactions, important for understanding soot formation. Furthermore, thermal effects induced by multiple consecutive pulses modify the optical properties of soot nanoparticles, thus making single-pulse imaging essential. Here, we report single-shot laser-sheet compressed ultrafast photography (LS-CUP) for billion-frames-per-second planar imaging of flame-laser dynamics. We observed laser-induced incandescence, elastic light scattering, and fluorescence of soot precursors - polycyclic aromatic hydrocarbons (PAHs) in real-time using a single nanosecond laser pulse. The spatiotemporal maps of the PAHs emission, soot temperature, primary nanoparticle size, soot aggregate size, and the number of monomers, present strong experimental evidence in support of the theory and modeling of soot inception and growth mechanism in flames. LS-CUP represents a generic and indispensable tool that combines a portfolio of ultrafast combustion diagnostic techniques, covering the entire lifecycle of soot nanoparticles, for probing extremely short-lived (picoseconds to nanoseconds) species in the spatiotemporal domain in non-repeatable turbulent environments. Finally, LS-CUP’s unparalleled capability of ultrafast wide-field temperature imaging in real-time is envisioned to unravel mysteries in modern physics such as hot plasma, sonoluminescence, and nuclear fusion.
CRIS-Team Scopus Importer:2023-03-10

Single-pulse ultrafast real-time simultaneous planar imaging of femtosecond laser-nanoparticle dynamics in flames - Mishra, Yogeshwar Nath; Wang, Peng; Bauer, Florian; Gudipati, Murthy S.; Wang, Lihong V. (Light: Science & Applications, 2024)
The creation of carbonaceous nanoparticles and their dynamics in hydrocarbon flames are still debated in environmental, combustion, and material sciences. In this study, we introduce single-pulse femtosecond laser sheet-compressed ultrafast photography (fsLS-CUP), an ultrafast imaging technique specifically designed to shed light on and capture ultrafast dynamics stemming from interactions between femtosecond lasers and nanoparticles in flames in a single-shot. fsLS-CUP enables the first-time real-time billion frames-per-second (Gfps) simultaneous two-dimensional (2D) imaging of laser-induced fluorescence (LIF) and laser-induced heating (LIH) that are originated from polycyclic aromatic hydrocarbons (PAHs) and soot particles, respectively. Furthermore, fsLS-CUP provides the real-time spatiotemporal map of femtosecond laser-soot interaction as elastic light scattering (ELS) at an astonishing 250 Gfps. In contrast to existing single-shot ultrafast imaging approaches, which are limited to millions of frames per second only and require multiple laser pulses, our method employs only a single pulse and captures the entire dynamics of laser-induced signals at hundreds of Gfps. Using a single pulse does not change the optical properties of nanoparticles for a following pulse, thus allowing reliable spatiotemporal mapping. Moreover, we found that particle inception and growth are derived from precursors. In essence, as an imaging modality, fsLS-CUP offers ultrafast 2D diagnostics, contributing to the fundamental understanding of nanoparticle’s inception and broader applications across different fields, such as material science and biomedical engineering.
CRIS-Team Scopus Importer:2024-09-13

Single-shot two-dimensional nano-size mapping of fluorescent molecules by ultrafast polarization anisotropy imaging - Wang, Peng; Mishra, Yogeshwar Nath; Bauer, Florian; Gudipati, Murthy S.; Wang, Lihong V. (Nature Communications, 2025)
Molecular size plays a crucial role in determining the physical, chemical, and biological properties of substances. However, traditional fluorescence polarization anisotropy methods struggle to capture fast transient processes or provide plane-specific details. To overcome these limitations, we introduce Compressed Ultrafast Planar Polarization Anisotropy Imaging (CUP2AI). This approach combines femtosecond laser-sheet illumination, molecular rotational diffusivity, and compressed sensing to enable real-time, non-invasive, wide-field anisotropy measurements in both liquid and gas phases. CUP2AI captures 2D molecular size mapping in a single acquisition, granting unprecedented insights into dynamic events across various excitation modes (i.e. both one- and two-photon) and environmental conditions. It enables mapping of molecular volume (500 Å³–80,000 Å³) and hydrodynamic diameter (10 Å–50 Å) based on anisotropy lifetimes. We imaged fluorescein-conjugated dextran in water and polycyclic aromatic hydrocarbons in flames. CUP2AI holds transformative potential for applications ranging from molecular biology and drug design to nanoparticle formation.
CRIS-Team Scopus Importer:2025-06-06

Temperature imaging during the hydrogen release reaction from a liquid organic hydrogen carrier (LOHC) system using phosphor thermometry - Bollmann, Jonas; Bauer, Florian; Keim, Silvan; Herz, Nikolas; Zigan, Lars; Wasserscheid, Peter; Will, Stefan (Experiments in Fluids, 2024)
Liquid organic hydrogen carrier (LOHC) systems offer a particularly interesting option for chemical hydrogen storage. In order to characterize and understand the endothermal hydrogen release from the carrier liquid and to evaluate suitable catalyst materials, knowledge of the temperature fields in the dehydrogenation reactor is important. One suitable technique for planar temperature sensing in reacting systems is phosphor thermometry. It is based on the excitation of a luminescent material by a laser pulse and detection of the subsequent phosphorescence signal. We investigated the luminescence of the thermographic phosphor (Sr,Ca)SiAIN3:Eu2+ (“SCASN:Eu2+”) dispersed in the H0-DBT / H18-DBT LOHC system in a temperature range from 400 to 600 K. A measurement cell enables repeatable and homogeneous measurement conditions of the hydrogen release reaction. A catalytic plate was put inside the heated LOHC. Temperature fields during the hydrogen release reaction were measured for the first time using the phosphorescence decay time (PDT) and the phosphorescence intensity ratio method (PIR). As expected, a strong cooling at the catalyst surface during the endothermal hydrogen release reaction could be observed, which was quantified to be in the range of 40 K. Graphical abstract: (Figure presented.).
CRIS-Team Scopus Importer:2024-08-23

Three‑dimensional particle size determination in a laminar diffusion flame by tomographic laser‑induced incandescence - Bauer, Florian; Yu, Tao; Cai, Weiwei; Huber, Franz; Will, Stefan (Applied Physics B-Lasers and Optics, 2020)
Non-intrusive measurement techniques are required to gain a comprehensive understanding about the processes of soot forma-tion, growth and oxidation. Time-resolved laser-induced incandescence (TiRe-LII), commonly performed 0D or 2D within a flame, has proven to be a very suitable tool for the in situ sizing of soot primary particles. In this work, the technique is expanded to the third dimension by employing volumetric illumination and coupling it with a tomographic approach, which allows to computationally gain 3D information from 2D images taken at various angles. To minimize experimental cost, an approach using nine fiber bundles arranged in a semicircle around the flame and imaging the light onto a single camera is used. The technique is demonstrated on an ethene diffusion flame on a standard burner, providing spatially resolved 3D particle sizes. One focus of this work is to reveal the influence of input parameters such as the local bath gas temperature, which we measured by two-color pyrometry, and local laser fluence, which are both required for an accurate evaluation of the local particle size. It is shown that the assumption of an average temperature may result in a wrong picture even of qualitative soot size evaluation. In the end, a concept is proposed for a simultaneous determination of the 3D distribution of particle sizes through TiRe-LII and the required bath gas temperature via two-color pyrometry using a tomographic approach with only three camera

Three-dimensional particle size determination in a laminar diffusion flame by tomographic laser-induced incandescence - Bauer, Florian; Yu, Tao; Cai, Weiwei; Huber, Franz; Will, Stefan (Applied Physics B-Lasers and Optics, 2021)

UV absorption cross sections of vaporized 1-methylnaphthalene at elevated temperatures - Retzer, Ulrich; Ulrich, Hannah; Bauer, Florian; Will, Stefan; Zigan, Lars (Applied Physics B-Lasers and Optics, 2020)
In this work, the UV absorption cross sections of the fluorescence tracer 1-methylnaphthalene are determined in the range of 230–330 nm. The experiments are performed in a continuously scavenged gas flow cell, which allows for defined homogeneous conditions regarding temperature, pressure, and tracer/fuel composition. A LDLS (laser driven light source) is used for irradiation, which enables high spectral emission intensities in the UV range studied. For detection, a spectrograph in combination with an intensified camera is applied. Absorption cross sections at temperatures up to 850 K are determined and compared to sparsely available published data. Possible uncertainties caused by the optical setup and the flow cell, respectively, are considered.<br